Epidemics and Peptide Vaccine Response: A Brief Review - Nandy, Ashesh; Dey, Sumanta; Roy, Proyasha; Basak, Subhash C. (Current Topics in Medicinal Chemistry, 2018)
We briefly review the situations arising out of epidemics that erupt rather suddenly, threatening life and livelihoods of humans. Ebola, Zika and the Nipah virus outbreaks are recent examples where the viral epidemics have led to considerably high degree of fatalities or debilitating consequences. The problems are accentuated by a lack of drugs or vaccines effective against the new and emergent viruses, and the inordinate amount of temporal and financial resources that are required to combat the novel pathogens. Progress in computational, biological and informational sciences have made it possible to consider design of synthetic vaccines that can be rapidly developed and deployed to help stem the damages. In this review, we consider the pros and cons of this new paradigm and suggest a new system where the manufacturing process can be decentralized to provide more targeted vaccines to meet the urgent needs of protection in case of a rampaging epidemic.
Keywords: Nipah virus